Strategi Remedial dalam Penyelesaian Pembiayaan Bermasalah Berbasis Akad Syariah pada Kantor Pusat KSPPS Borobudur Magelang - Gita Eka Nur Cahyani; Siti Afidatul Khotijah (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Financing is one of the main activities in Islamic financial institutions that plays an important role in supporting the economic activities of members. However, in practice, financing does not always run smoothly and may lead to financing problems due to delays in payment by members. This study focuses on the implementation of remedial strategies in resolving problematic financing based on sharia contracts at the Head Office of KSPPS AL-HUSNA Borobudur, Magelang. This research employs a qualitative approach using a case study method. Data were obtained through observation, interviews, and documentation with parties involved in financing management at the Head Office of KSPPS AL-HUSNA Borobudur. The results indicate that the resolution of problematic financing is carried out through remedial strategies that include approaches to members, persuasive collection efforts, and adjustments or rescheduling of payments. The implementation of these strategies is expected to help the cooperative address financing problems and ensure the smooth flow of cooperative funds.